The conceived proposal for the role of Saudi universities in imparting the values of digital life to their students - Khatmah Hassan Hamod Mohamad (RES MILITARIS, 2022)
The current study sought to present a proposed perception of the role of Saudi universities in imparting the values of digital life to their students, By learning about values and how to provide university students with values in light of the challenges of digital life, The study used to achieve its objectives through the procedures of the descriptive analytical approach, For its suitability for such type of studies, The study concluded that the requirements for this perception are that Saudi universities have a pioneering role in serving the Saudi society, By preserving societal values, enhancing and imparting new values, and supporting students’ skills in their scientific and practical lives, to complete the comprehensive development process.